Thermostable alpha-amylase from moderately halophilic Halomonas sp AAD21 - SARIYAR AKBULUT, BERNA; KAZAN, DİLEK (TUBITAK SCIENTIFIC & TECHNICAL RESEARCH COUNCIL TURKEY, 2012)
The moderately halophilic Halomonas sp. strain AAD21, which produces extracellular thermostable alpha-amylase, was isolated from the Camalti Saltern area located in Izmir, Turkey. NaCl, carbon, and nitrogen sources in the growth medium were optimized to enhance alpha-amylase yield. The highest enzyme yield was measured in the presence of 20% NaCl with peptone as the nitrogen and starch as the carbon sources in the fermentation broth. This microorganism was also found to utilize waste potato peel as a carbon source for alpha-amylase production. Concentrations of carbon and nitrogen sources were optimized using a statistical approach, and alpha-amylase activity increased from 4.07 U mL(-1) min(-1) to 26.25 U mL(-1) min(-1). Maximum alpha-amylase production was achieved at the end of 48 h of growth in the presence of 20% NaCl, 4.12% starch, 1.0% peptone, 0.2% KCl, 2% MgSO4 center dot 7H(2)O, and 0.03% trisodium citrate pentahydrate. The optimum pH and temperature of the alpha-amylase were found to be 7.0 and 50 degrees C, respectively. The alpha-amylase synthesized by Halomonas sp. AAD21 was also thermostable. Crude alpha-amylase did not lose its original activity after 2 h of incubation at 50 degrees C and 60 degrees C, and it retained 70% of its original activity after 120 min of incubation at 90 degrees C.
Keywords: Moderate halophile; Halomonas sp AAD21; alpha-amylase; thermostable; optimization; XYLANASE PRODUCTION; PURIFICATION